2014
DOI: 10.4317/medoral.19626
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser effect in patients with neurosensory impairment of mandibular nerve after sagittal split ramus osteotomy. Randomized clinical trial, controlled by placebo

Abstract: Objectives: Evaluate the effect on the application of low level laser therapy, in patients that have been previously intervened with a sagittal ramus split osteotomy and present neurosensory impairment due to this surgery, compared with placebo. Study Design: This preliminary study is a randomized clinical trial, with an experimental group (n=17) which received laser light and a control group (n=14), placebo. All participants received laser applications, divided after surgery in days 1, 2, 3, 5, 10, 14, 21 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
1
24
0
15
Order By: Relevance
“…It should be pointed out that laser treatment is not indicated for nerve transections; the only effective treatment for nerve discontinuity defects or total lack of impulse transmission is microsurgical repair. 22 Although there are different treatment options for paresthesia after orthognathic surgery, LLLT is used largely to restore neuronal function. The main effects of LLLT irradiation are an increase in b-endorphin production and neurotransmission, pain relief, and increased blood flow, thus allowing for drainage of substances from inflammation and its consequent regulation, in addition to accelerated tissue repair, bone regeneration, and re-establishment of neural function.…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that laser treatment is not indicated for nerve transections; the only effective treatment for nerve discontinuity defects or total lack of impulse transmission is microsurgical repair. 22 Although there are different treatment options for paresthesia after orthognathic surgery, LLLT is used largely to restore neuronal function. The main effects of LLLT irradiation are an increase in b-endorphin production and neurotransmission, pain relief, and increased blood flow, thus allowing for drainage of substances from inflammation and its consequent regulation, in addition to accelerated tissue repair, bone regeneration, and re-establishment of neural function.…”
Section: Discussionmentioning
confidence: 99%
“…Gasperini et al, em 2014 mostra que houve uma melhora na sensibilidade do lábio inferior e do mento em todos os pacientes, ambos os lados irradiados e não-irradiados, porém o lado irradiado se recuperou mais rapidamente e quase completamente no período de 60 dias pós-cirúrgio. Já Führer-Valdivia et al, (2014) relataram diferença entre os pacientes irradiados e não-irradiados, o resultado mais expressivo foi a sensibilidade geral avaliada pela Escala Visual Analógica (VAS) que demonstrou a recuperação normal alcançada por um grande número de pacientes do grupo que recebeu a terapia com laser (68,75%) contra apenas um pequeno número de pacientes tratados apenas com placebo (21,43%) seis meses após a cirurgia. Isso sugere que o tratamento com laser de baixa potência é eficaz na aceleração do reparo neurossensorial do nervo alveolar inferior devido aos estresses mecânicos causados pela osteotomia sagital do ramo mandibular.…”
Section: Em Seu Trabalhounclassified
“…46 Neurosensory recovery. Neurosensory recovery was assessed in nine studies; six studies after mandibular ramus osteotomy, [47][48][49][50][51][52] and three of them after various oral surgeries [53][54][55] (Table 2). Six studies represented a wide range of effective PBM parameters for nerve recovery after mandibular ramus osteotomy (wavelength: 632-830 nm; power: 20-100 mW; energy density: 2-32 J/cm 2 ).…”
Section: Study Selectionmentioning
confidence: 99%
“…Six studies represented a wide range of effective PBM parameters for nerve recovery after mandibular ramus osteotomy (wavelength: 632-830 nm; power: 20-100 mW; energy density: 2-32 J/cm 2 ). [47][48][49][50][51][52] In addition, three other studies showed positive impact of PBM on inferior alveolar nerve (IAN) paresthesia after various oral surgeries such as orthognathic surgery. [53][54][55] de Oliveira et al, 54 in a 3year retrospective study, reported that gallium, aluminum, arsenide (GaAlAs) diode 808 nm at 100 mW and 100 J/cm 2 was more effective than placebo in treating IAN paresthesia.…”
Section: Study Selectionmentioning
confidence: 99%